Chronic low dose organic arsenic induced liver structural damage - Saharudin, Shahida; Abdullah, Nor Zamzila; A. Talib, Norlelawati; Ab Rahman, Jamalludin; Abd. Fuaat, Azliana; Buyong, Zunariah (IIUM Press, 2020)
Introduction: Over the decades, organic arsenic has been thought to be less toxic than inorganic arsenic. Monosodium methylarsonate (MSMA) is a potent organoarsenical herbicide that is still being used in most Asian countries. Reported studies on the effects of organic arsenic are mainly to the gastrointestinal system, however there are limited research on its impacts to the liver. Therefore, this study aimed to investigate the effect of MSMA exposure on hepatocytes and liver sinusoidal endothelial cells (LSEC). Materials and Methods: Fourteen Sprague Dawley rats (n=14) were divided equally into arsenic-exposed (n=7) and control (n=7) groups. The rats in arsenic-exposed group were given MSMA at 63.20 mg/kg daily for 6 months through oral gavage. While the rats in control group were given distilled water ad libitum. At the end of the duration, they were euthanized and underwent liver perfusion for tissue preservation. Liver tissues were harvested and processed for light microscopy, scanning and transmission electron microscopy. The findings were analysed descriptively. Results: MSMA had caused necrotic and apoptotic changes to the liver. Normal organelles morphology were loss in the hepatocytes while LSEC revealed defenestration. Conclusion: In this study, chronic low dose organic arsenic exposure showed evidence of toxicity to hepatocytes. Interestingly, LSEC demonstrated capillarization changes.